Analisis perhitungan harga pokok produksi dengan menggunakan metode full costing pada UKM Nona - Soeliongan, Christofel D.; Karamoy, Herman; Latjandu , Lady Diana (Yayasan Widyantara Nawasena Raharja, 2024)
Determination of cost of production is a method used in collecting production costs consisting of direct raw materials, direct labor, and factory overhead costs plus product inventory in the initial process and less product inventory in the final process. This study aims to determine the application of determining the cost of production using the full costing method, in UKM Nona. This method determines the cost of products which takes into account all elements of production costs consisting of raw materials, direct labor costs and factory overhead costs, both fixed and variable. The selling price can be obtained from the cost of production plus the expected profit. This research uses descriptive research method. The results of this study indicate that the calculation of the cost of production using the full costing method obtains a higher cost of goods compared to the calculation of UKM.